A Transgenic Mouse Model of OI Type V Supports a Neomorphic Mechanism of the IFITM5 Mutation. (16th February 2015) - Lietman, Caressa D; Marom, Ronit; Munivez, Elda; Bertin, Terry K; Jiang, Ming‐Ming; Chen, Yuqing; Dawson, Brian; Weis, Mary Ann; Eyre, David; Lee, Brendan
ABSTRACT: Osteogenesis imperfecta (OI) type V is characterized by increased bone fragility, long bone deformities, hyperplastic callus formation, and calcification of interosseous membranes. It is caused by a recurrent mutation in the 5' UTR of the IFITM5 gene (c.‐14C > T). This mutation introduces an alternative start codon, adding 5 amino acid residues to the N‐terminus of the protein. The mechanism whereby this novel IFITM5 protein causes OI type V is yet to be defined. To address this, we created transgenic mice expressing either the wild‐type or the OI type V mutant IFITM5 under the control of an osteoblast‐specific Col1a1 2.3‐kb promoter. These mutant IFITM5 transgenic mice exhibited perinatal lethality, whereas wild‐type IFITM5 transgenic mice showed normal growth and development. Skeletal preparations and radiographs performed on E15.5 and E18.5 OI type V transgenic embryos revealed delayed/abnormal mineralization and skeletal defects, including abnormal rib cage formation, long bone deformities, and fractures. Primary osteoblast cultures, derived from mutant mice calvaria at E18.5, showed decreased mineralization by Alizarin red staining, and RNA isolated from calvaria showed reduced expression of osteoblast differentiation markers such as Osteocalcin, compared with nontransgenic littermates and wild‐type mice calvaria, consistent with the in vivo phenotype. Importantly, overexpression of wild‐type Ifitm5 did not manifest a significant bone phenotype. Collectively, our results suggest that expression of mutant IFITM5 causes abnormal skeletal development, low bone mass, and abnormal osteoblast differentiation. Given that neither overexpression of the wild‐type Ifitm5, as shown in our model, nor knock‐out of Ifitm5, as previously published, showed significant bone abnormalities, we conclude that the IFITM5 mutation in OI type V acts in a neomorphic fashion. © 2014 American Society for Bone and Mineral Research.